2014
DOI: 10.1016/j.yjmcc.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

MMI-0100 inhibits cardiac fibrosis in myocardial infarction by direct actions on cardiomyocytes and fibroblasts via MK2 inhibition

Abstract: The cell-permeant peptide inhibitor of MAPKAP kinase 2 (MK2), MMI-0100, inhibits MK2 and downstream fibrosis and inflammation. Recent studies have demonstrated that MMI-0100 reduces intimal hyperplasia in a mouse vein graft model, pulmonary fibrosis in a murine bleomycin-induced model and development of adhesions in conjunction with abdominal surgery. MK2 is critical to the pathogenesis of ischemic heart injury as MK2 −/− mice are resistant to ischemic remodeling. Therefore, we tested the hypothesis that inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 77 publications
1
42
1
Order By: Relevance
“…We initially dosed at 25 mg/kg daily for 6 days (during the period of early surgical recovery) and subsequently ramped up to 50 mg/kg daily until postoperative day 28 (a time point when robust pathologic remodeling of the remote LV myocardium is present in this model) (protocol in Fig. 2A) (35). Similar to our findings in the pressure overload treatment model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We initially dosed at 25 mg/kg daily for 6 days (during the period of early surgical recovery) and subsequently ramped up to 50 mg/kg daily until postoperative day 28 (a time point when robust pathologic remodeling of the remote LV myocardium is present in this model) (protocol in Fig. 2A) (35). Similar to our findings in the pressure overload treatment model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cultured fibroblasts treated with AngII showed that p38 activation was necessary for fibrosis while TGFβ prolonged p38-dependent increases in the expression of matrix proteins like collagen and fibronectin, as well as αSMA 11, 41, 42 . Our in vitro assays place p38 downstream of extracellular signals like TGFβ, AngII, but upstream of known myofibroblast regulatory factors such as calcineurin, TRPC6, MK2, and SRF 11, 21, 39, 40 . The temporal, lineage, and injury dependent activation of these combined molecular regulators will thus ultimately determine fibroblast function and hence the degree of fibrosis and its temporal persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were scanned using an Aperio ScanScope (Aperio Technologies, Vista, CA) and fibrosis was quantified using Aperio ImageScope (v12.3.2.8013). The Positive Pixel Count v9 algorithm was used to measure staining of collagen (representing both fibrosis and collagen in extracellular matrix [ECM]), with hue value and width of 0.66 and 0.1, respectively 29. The N positive/N total value representing the percentage of collagen of the entire section was used to determine the weighted average for each slide, expressed as percentage of fibrosis.…”
Section: Methodsmentioning
confidence: 99%